Book Review of Looking at Trauma: A Tool Kit for Clinicians - Bezanson, Birdie J. (Canadian Journal of Counselling and Psychotherapy, 2024)
This book review looks at a clinical tool kit that provides a solid conceptual foundation in trauma care. The editors have drawn on the expertise of psychotherapists, psychological associates, psychiatrists, social workers, and a medical illustrator. The unique approach offers a resource to paraprofessionals, professionals, and anyone working in settings where trauma is a necessary consideration. The tool kit provides practice information for psychoeducation and guidance on how to develop strategies to manage the effects of complex trauma. The primary goal is to build community capacity in an already overburdened mental health system.